Antibody modified gold nanoparticles for fast colorimetric screening of rheumatoid arthritis. Issue 11 (9th May 2019) - Veigas, Bruno; Matias, Ana; Calmeiro, Tomás; Fortunato, Elvira; Fernandes, Alexandra R.; Baptista, Pedro Viana
Abstract : Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic joint inflammation and one of the main causes of chronic disability worldwide with high prevalence in the ageing population. Abstract : Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic joint inflammation and one of the main causes of chronic disability worldwide with high prevalence in the ageing population. RA is characterized by autoantibody production, synovial inflammation and bone destruction, and the most accepted biomarker is rheumatoid factor (RF) autoantibodies. In this work, we developed a low-cost approach for the detection and quantification of the RF marker. This colorimetric immunosensor is based on gold nanoprobe crosslinking that results in extensive aggregation in the presence of the pentameric IgM RF. Aggregation of the nanoconjugates yields a color change from red to purple that can be easily observed by the naked eye. The interaction between nanoconjugates and the specific target was confirmed via dynamic light scattering (DLS), Raman spectroscopy and atomic force microscopy (AFM) imaging. This conceptual system shows a LOD of 4.15 UA mL −1 IgM RF (clinical threshold is set for 20 IU mL −1 ). The one-step biosensor strategy herein proposed is much faster than conventional detection techniques, without the need for secondary antibodies, additional complex washing or signal amplification protocols. To the best of our knowledge this is the first report on target induced aggregation of gold nanoprobes for quantitative colorimetric autoantibody detection.